Household’s food consumption decisions, impacts, synergies, and trade-offs on food system outcomes: Empirical evidence from Northern Vietnam - Hernandez, Ricardo (2024)
This presentation was displayed during the 5th International Global Food Security Conference, as part of the work of the CGIAR Research Initiative on Sustainable Healthy Diets through Food Systems Transformation (SHiFT). This work has also been supported by the “Missing Middle project funded by NWO-WOTRO (Grant number W07.303.109)”.